Emissions impacts of electrifying motorcycle taxis in Kampala, Uganda. (March 2022) - Vanatta, Max; Rathod, Bhavesh; Calzavara, Jacob; Courtright, Thomas; Sims, Teanna; Saint-Sernin, Étienne; Clack, Herek; Jagger, Pamela; Craig, Michael
Abstract: Large fleets of motorcycle taxis in Kampala, Uganda, and other cities in low and middle-income countries (LMICs) emit significant local and global air pollutants. To reduce emissions, companies have started selling electric motorcycles. We quantify the use-phase emissions impact of electrifying motorcycle taxis by processing real-world trip and charging data from Kampala, then estimating charging-caused emissions with an economic dispatch model of the Ugandan power system. We then compare these emissions to tank-to-wheels estimates of conventional motorcycles over the same trips. We find that electrifying gas-powered motorcycle taxis would reduce carbon dioxide (CO2 ), carbon monoxide (CO), nitrogen oxide (NOx ), and hydrocarbon emissions by 36%, 90%, 58%, and 99%, respectively, but increase sulfur oxide (SOx ), particulate matter 10 μm or less (PM10 ), and particulate matter 2.5 μm or less (PM2.5 ) emissions by 870%, 109%, and 97%, respectively. PM and SOx emission increases stem from generation at bagasse and heavy fuel oil (HFO) point sources far from load centers. Additionally, we find seasonality of the charging associated emissions due to dominance of hydropower in the Ugandan grid. Overall, we find clear and potential local air pollution benefits of electrifying motorcycle taxis in Kampala.